Fetal Mammalian Heart Generates a Robust Compensatory Response to Cell Loss. Issue 2 (14th July 2015) - Sturzu, Anthony C.; Rajarajan, Kuppusamy; Passer, Derek; Plonowska, Karolina; Riley, Alyssa; Tan, Timothy C.; Sharma, Arun; Xu, Adele F.; Engels, Marc C.; Feistritzer, Rebecca; Li, Guang; Selig, Martin K.; et al.
<x xml:space="preserve">Abstract</x> Background— Heart development is tightly regulated by signaling events acting on a defined number of progenitor and differentiated cardiac cells. Although loss of function of these signaling pathways leads to congenital malformation, the consequences of cardiac progenitor cell or embryonic cardiomyocyte loss are less clear. In this study, we tested the hypothesis that embryonic mouse hearts exhibit a robust mechanism for regeneration after extensive cell loss. Methods and Results— By combining a conditional cell ablation approach with a novel blastocyst complementation strategy, we generated murine embryos that exhibit a full spectrum of cardiac progenitor cell or cardiomyocyte ablation. Remarkably, ablation of up to 60% of cardiac progenitor cells at embryonic day 7.5 was well tolerated and permitted embryo survival. Ablation of embryonic cardiomyocytes to a similar degree (50% to 60%) at embryonic day 9.0 could be fully rescued by residual myocytes with no obvious adult cardiac functional deficit. In both ablation models, an increase in cardiomyocyte proliferation rate was detected and accounted for at least some of the rapid recovery of myocardial cellularity and heart size. Conclusion— Our study defines the threshold for cell loss in the embryonic mammalian heart and reveals a robust cardiomyocyte compensatory response that sustains normal fetal development.